Want to start a revolution? : radical women in the black freedom struggle. - Gore, Dayo F. (NYU Press, 2009)
The story of the black freedom struggle in America has been overwhelmingly male-centric, starring leaders like Martin Luther King, Jr., Malcolm X, and Huey Newton. With few exceptions, black women have been perceived as supporting actresses; as behind-the-scenes or peripheral activists, or rank and file party members. But what about Vicki Garvin, a Brooklyn-born activist who became a leader of the National Negro Labor Council and guide to Malcolm X on his travels through Africa? What about Shirley Chisholm, the first black Congresswoman?. From Rosa Parks and Esther Cooper Jackson, to Shirley G.